Penerapan model pembelajaran problem based learning untuk meningkatkan pemahaman materi indonesia kaya budaya pada peserta didik kelas 4 sekolah dasar - Prima Aldi Kurnia; siti istiyati; fadhil purnama adi (Universitas Sebelas Maret, 2025)
This study aims to improve understanding of Indonesia's Rich Culture material by using the Problem Based Learning learning model for students SD Negeri 2 Kuwarisan Kebumen. This research approach is qualitative with the type of research, Classroom Action Research (PTK). The research that has been carried out has two cycles. Each cycle has two meetings. Each meeting has planning, action, and reflection. The subjects of this research are fourth grade students of SD Negeri 2 Kuwarisan. Data collection techniques include interviews, observation, documentation and tests. The validity test technique uses technical triangulation. Data analysis techniques use interactive data analysis models from Miles and Huberman. Data analysis begins with data collection, data reduction, data presentation and data conclusions taken during the research. The results showed an increase in understanding of Indonesia's Rich Culture material by using the Problem Based Learning learning model. This can be seen in the increase in the percentage of students who meet the minimum completeness criteria (KKM) at the pre-action stage, cycle I, cycle II. The pre-action activities of students who have met the minimum completeness criteria (KKM) in understanding the material of Indonesia Kaya are 35.71% or there are 5 students. While students who have not met the minimum completeness criteria (KKM) are 64.07% or there are 9 students. In cycle I, students who have met the minimum completeness criteria (KKM) are 42.855 or there are 12 students. While 57.14% or 16 learners have not reached the minimum completeness criteria (KKM). In cycle II as many as 17.85% or there are 5 students who have not met the minimum completeness criteria (KKM) while for students who have met the minimum completeness criteria (KKM) as many as 82.14% or there are 23 students. The conclusion of this study is that the use of the Problem Based Learning learning model can improve understanding of IPAS learning material Indonesia is rich in culture.